YpT0N+ status in oesophageal cancer patients: Location of residual metastatic lymph nodes with regard to the neoadjuvant radiation field. Issue 3 (March 2019) - Schurink, B.; Seesing, M.F.J.; Goense, L.; Mook, S.; Brosens, L.A.A.; Mohammad, N. Haj; Ruurda, J.P.; Roeling, T.A.P.; Bleys, R.L.A.W.; van Hillegersberg, R.
Abstract: Introduction: A subset of oesophageal cancer patients has residual nodal disease despite complete pathologic response of the primary tumour after neoadjuvant chemoradiation and resection. The aim of this study was to determine the exact location of metastatic nodes with regard to the neoadjuvant radiation field and to assess progression-free (PFS) and overall survival (OS) in this group of patients. Materials and methods: From January 2010 to January 2017, complete tumour responders (ypT0) after neoadjuvant chemoradiotherapy and oesophagectomy were identified from a prospective database and grouped according to residual nodal disease (ypT0N + or ypT0N0). Radiation fields were analysed for location of the metastatic nodes and PFS and OS were determined. Results: In a total of 192 patients, 53 complete responders (ypT0) were identified. Of those, 11 patients (20.8%) were ypT0N+ with a total of 12 metastatic nodes: 8 (66.7%) located within the neoadjuvant radiation field and 4 (33.3%) located outside this field. Although not statistically significant, 1- and 2-year PFS were worse in ypT0N + patients (ypT0N+ 64.3% vs. ypT0N0 84.4%; ypT0N+ 48.2% vs. ypT0N0 80.7%, respectively; p = 0.051), just as 1- and 2-year OS rates, however, to a lesser extent (ypT0N+ 75.0% vs. ypT0N0 76.3%; ypT0N+ 75.0% vs. ypT0N0 72.9%, respectively; p = 0.956). Conclusion: Most ypT0N + lymph nodes are located within the neoadjuvant radiation field. Although a small heterogeneous population was included, this might be due to an inadequate response to neoadjuvant chemoradiotherapy leading to a trend towards worse PFS and OS in ypT0N + patients. Larger studies need to validate our findings.